Ответы и объяснения

2012-10-30T13:35:15+00:00

x^2-xy+y^2=63
x+y=-3

x^2-xy+y^2=63
x=(-3)-y

x^2-xy+y^2=63
x=-3-y

(-y-3)^2-(-y-3)*y+y^=63
x=-y-3

 

Случай 1:

 

y=-6

x=-y-3

y=-6
y=-(-6)-3

 

y=-6

x=3

 

Случай 2:

y=3

x=-y-3

 

y=3

x=-3-3

 

y=3

x=-6

 

Окончательный ответ:

x=3

y=-6

 

x=-6

y=3

Вторая система:

2x+y=3

x^2+y^2-6y=36

 

y=3-2x

x^2+y^2-6y=36

 

y=-2x+3

x^2+(-2x+3)^2-6(-2x+3)=36

 

Случай 1:
y=-2x+3

x= -3

 

y=-2(-3)+3

x=-3

 

y=9

x=-3

 

Случай 2:

y=-2x+3

x=3

 

y=-2*3+3

x=3

 

y=-3

x=3

 

Окончательный ответ:

x=-3

y=9

 

x=3

y=-3